Diet and Endometriosis: An Umbrella Review - Lenycia C. L. Neri; Federica Quintiero; Simona Fiorini; Monica Guglielmetti; Ottavia Eleonora Ferraro; Anna Tagliabue; Barbara Gardella; Cinzia Ferraris (Foods, 2025)
The association between nutrition and endometriosis is controversial. This umbrella review aimed to investigate whether specific dietetic strategies are useful for reducing endometriosis risk/symptoms. Systematic reviews on diet therapies for endometriosis were analyzed using the Joanna Briggs Institute (JBI) Manual for Evidence Synthesis methodology, and an umbrella review was implemented using Jamovi software. The 10 included systematic reviews comprised observational studies (cohort, case–control, cross-sectional) and interventional trials (randomized, non-randomized). A mild (class IV, lowest strength on evidence quartile) protective effect on vegetables (RR 0.590; 95% CI 0.49–0.71 p < 0.001), cheese (OR 0.840; 95% CI 0.74–0.96 p = 0.011), total dairy (RR 0.874; 95% CI 0.81–0.95 p = 0.001), and high-fat dairy (RR 0.590; 95% CI 0.81–0.99 p = 0.025) was found. Butter (RR 1.266; 95% CI 1.03–1.55 p = 0.024) and high caffeine (>300 mg/day) (RR 1.303; 95% CI 1.05–1.62 p = 0.019) consumption increased the risk of endometriosis. Other food groups had low-quality evidence due to limited studies. A higher intake of vegetables and dairy products may reduce the risk and/or symptoms of endometriosis, while a high intake of caffeine and butter may increase the risk. However, the heterogeneity across studies is significant, and the overall quality of the findings is low. Therefore, it is crucial to conduct new research in this field, focusing on well-designed randomized trials.